Outward activity of multinationals by industrial sector - ISIC Rev. 4 (Edition 2021) (OECD Statistics on Measuring Globalisation, 2021)
This dataset provides statistics on outward activity of multinationals by industrial sector with figures on the activity affiliates located abroad (total exports, value added, turnover, gross operating surplus)by industry according to the International Standard Industrial Classification (ISIC Revision 4). Data are presented from 2007 onwards